The impact of traveling on infectious diseases transmission with a focus on air travel: A Narrative Review. - Aghayan, Seyed Kiarash; hosseinzadeh, Fazel Moghadas (International Journal of Travel Medicine & Global Health, 2025)
The global tourism industry has experienced significant growth from 2009 to 2014, with international tourist arrivals increasing from 25.3 million in 1950 to 1.138 billion in 2014. This surge in travel, projected to grow at an annual rate of 6%, has implications for public health, particularly concerning the spread of infectious diseases. Travelers can act as carriers of pathogens, introducing them to new regions, often without showing symptoms. EIDs pose a considerable threat, exacerbated by increased global mobility and urbanization. Air travel, in particular, has facilitated the rapid transmission of diseases like SARS and influenza, highlighting the need for effective public health measures to mitigate risks. The interconnectedness of travel networks and infectious disease dynamics is evident, as pathogens can be transported across vast distances, leading to outbreaks in previously unaffected areas. Factors influencing disease transmission include human demographics, environmental changes, and technological advancements. The introduction of pathogens into new populations can lead to outbreaks, especially when immunity is lacking. Understanding the interplay between human mobility and infectious disease transmission is crucial for developing strategies to prevent and control outbreaks in an increasingly mobile world.